Legal Foundation of the Security of Information-oriented Society - A. A. Yakovenko (Московский журнал международного права, 2007)
In the introduction the author points out that widespread application of modern information technologies enhances the development of the economy but simultaneously poses new threats and challenges to the society. This circumstance leads to the necessity of developing new legal methods for protection of the state interests and the interests of the society.The author states that according to the research done by the United States Institute for Peace (USIP) the Internet is a perfect environment for the criminal activity as access to it is relatively easy, laws do not function there, there is no police. In this situation it is clear that global relations in the aspect of information should be governed by law for the purposes of protection of its subjects. International community and states individually had undertaken several steps towards the elaboration of legal norms to provide security of the emerging information-oriented society. For example, the UN General Assembly adopted the Resolution 53/70 concerning cyber crimes, cyber terrorism and cyber war. Similar steps are also taken on the national level.The other crucial issue in this sphere is the necessity of certain control over the information on the Internet. This is a controversial issue due to the right of an individual to a free access to the information. The author suggests creating the criteria for distinguishing Internet resources advocating xenophobia, racial and religious intolerance, etc.Thus the author comes to a conclusion that the threat to information security is an acute and complicated problem which cannot be resolved by states separately and requires their cooperation. Further the author focuses on the measures of combating cyber crimes and securing the information. The implementation of these measures, in author's opinion, will help to create an effective system of protection of the information-oriented society from the threats of cyber crime.